The impact of menopause on bone, zoledronic acid, and implications for breast cancer growth and metastasis - Hadji, P. (Oxford University Press, 2012)
Recent data from the AZURE, ABCSG-12, and ZO-FAST clinical trials have challenged our understanding of the potential anticancer activity of zoledronic acid (ZOL). Although the results of these studies may appear to be conflicting on the surface, a deeper look into commonalities among the patient populations suggest that some host factors (i.e. patient age and endocrine status) may contribute to the anticancer activity of ZOL. Indeed, data from these large clinical trials suggest that the potential anticancer activity of ZOL may be most robust in a low-estrogen environment. However, this may be only part of the story and many questions remain to be answered to fully explain the phenomenon. Does estrogen override the anticancer activity of ZOL seen in postmenopausal women? Are hormones other than estrogen involved that contribute to this effect? Does the role of bone turnover in breast cancer (BC) growth and progression differ in the presence of various estrogen levels? Here, we present a review of the multitude of factors affected by different endocrine environments in women with BC that may influence the potential anticancer activity of ZOL.